Four Early Christian Documents from Egypt Regarding Prayer to the Holy Spirit - Paschke, Boris (Pneuma, 2022)
Thus far, the topic of early Christian prayer to the Holy Spirit has not received much scholarly attention. Only a few studies are available that present relevant primary sources (Tertullian, De baptismo 8; Origen, Hom. Lev. I 1; Acts of John 94 and 96; Acts of Thomas 27 and 50; Phōs Hilaron). This article discusses four documents from ancient Egypt that are absent from these studies. The apocryphal writing The Ascension of Isaiah (5:14) is a witness to second-century early Christian (and perhaps also first-century Jewish) prayer to the Holy Spirit. Clement of Alexandria’s Pedagogue (3.12.101.1–2) dates from around 190 CE and provides very early evidence for liturgical prayer of thanksgiving addressed to the entire Trinity, with express reference to the Holy Spirit. The Apostolic Tradition dates from approximately the same time and contains several references to laudatory (eucharistic) prayers to the Trinity. In spite of its similar wording, the Papyrus Oxyrhynchus 1786 from the late third century CE is probably not to be considered a witness to praying to the Holy Spirit.